Synthesis and Characterization of Taper-Like ZnS Nanostructure and its Photoluminescence - Gong, Jiangfeng; Zhu, Weihua; Zhang, Kaixiao; Liu, Mingyi; Xie, Haiyan (Asian Journal of Chemistry, 2011)
We report the synthesis and characterization of ZnS nanostructures, which were grown by thermal evaporation of the ZnS powders at high temperature using iron network as the collection substrate. Scanning electron microscopy investigations show that the products present taperliked morphologies. Transmission electron microscopy studies indicate that the ZnS nanostructures are well crystallized. The formation mechanism of the novel nanostructure is discussed on the basis of the experimental results. The nanostructure is formed due to a fast growth of ZnS nanowire along [0001] and the subsequent "epitaxial" radial growth of the ZnS nanocone along the six (01-10) surfaces around the nanowire. A strong room-temperature photoluminescence in ZnS nanostructures has also been demonstrated.